ECOLOGICAL FUNCTIONS OF FISH BYPASS CHANNELS IN STREAMS: MIGRATION CORRIDOR AND HABITAT FOR RHEOPHILIC SPECIES. (16th December 2011) - Pander, J.; Mueller, M.; Geist, J.
ABSTRACT The introduction of weirs into stream ecosystems resulted in modifications of serial continuity and in the decline of riverine fish species. Successful river restoration requires information on the ecological functionality of fish bypass channels that are considered an ecological improvement according to the European Water Framework Directive. In this study, we compared the functionality of three nature‐oriented fish passes as compensatory habitats and migration corridors for fishes. Fish passes differed significantly from upstream and downstream reaches of the weirs, revealing higher current speed, lower water depth, smaller channel width and greater habitat variability. Following these structural differences, they provided key habitats for juvenile, small and rheophilic fishes that are typically underrepresented in highly modified water bodies. All fish passes were used as migration corridors, with increased fish movements during high discharge and at spawning periods. Because river stretches with high variability of current speed and water depth are scarce in highly modified water bodies, fish passes can play an important role as compensatory habitats and should thus be considered more intensively in habitat assessments and river restoration. Ideally, fish bypasses should mirror the natural discharge dynamics and consider all occurring fish species and sizes. Copyright © 2011 John Wiley & Sons, Ltd.